Simulation of the Potential Effectiveness of Decarbonization Policy at the Municipal Level in Kanagawa Prefecture, Japan - Kazumasa Nagamori; Toshihiko Masui (Chemical Engineering Transactions)
Many local governments in Japan have announced their intention to achieve net-zero carbon dioxide (CO2) emissions by 2050. This research used the Extended Snapshot model to simulate out to 2050 the potential effectiveness of decarbonization policy implementation in the 33 municipalities that comprise Kanagawa Prefecture, Japan: the results clarify how the sector-level characteristics of the individual municipalities could affect decarbonization outcomes, particularly with respect to the transportation, residential, and commercial sectors. This paper shows that the impact of decarbonization policy on emissions reductions differed depending on which sectors were the most developed in a given municipality, suggesting that when implementing climate change actions at the municipal level, consideration should be given to the local sectoral profile and assessments should be made of which policy options are likely to be the most effective. For example, to reduce energy-related CO2 emissions, municipalities expecting population growth may want to focus on policies in the residential sector, whereas municipalities with a developed tourist industry may want to focus on policies in the commercial sector. The present analysis indicates that, to realize net-zero municipalities through the implementation of decarbonization policy at the prefectural level, it will be necessary to develop inter-municipality collaborations with other prefectures, for example, for the import and export of renewable energy. In addition, achieving negative emissions in some municipalities will help achieve decarbonization goals at the prefectural and national levels.